O Ministério Público na atuação sociomediadora do direito à saúde: participação no processo de políticas públicas - VASCONCELOS, Roberta Silva (2019)
This study deals with the performance of the Public Prosecutor's Office regarding the implementation of the right to health, with emphasis on the sociomediary performance, understood as the one that comes before judicialisation. Throughout the research, a historical overview of the right to health in Brazil is established, explaining how the brazilian Health System and other regulatory frameworks have been reached since the Federal Constitution of 1988. In addition, an analysis is made of the Ministry Public in Brazil, as an institution, as well as the existing instruments for extrajudicial action in the field of health, with emphasis on the design of new instruments, in addition to the existing ones, based on the need for resolutive and democratic action. Regarding the methodological course, in the qualitative research, the technical procedures used focused on the bibliographical and documentary research, complemented by a semi-structured interview and participant observation in the empirical space of the research. In the bibliographical research, we searched the works focused on the analysis of the theme, with focus for the Public Prosecution in the realization of the right to health; the documentary research was developed seeking administrative procedures in process at the 18th Specialized Justice Department of Defense for Health of São Luís, the empirical space of the research. For theoretical foundation of the investigation and the exposition of the results, Pierre Bourdieu was used, mainly the categories of field, symbolic power, symbolic violence and radical doubt; From Robert Alexy, we sought the weighting technique and Michael Foucault was considered his contribution in the order of the speech. It was concluded by the existence of contradictions and crises inherent in the performance of members of the Public Prosecution Service, as well as by the need to rethink the traditional instruments of action, with the purpose of encouraging popular participation in this process.